2022
DOI: 10.1093/ehjopen/oeac003
|View full text |Cite
|
Sign up to set email alerts
|

Time to initiation of lipid-lowering drugs for subclinical atherosclerosis: sub-study of VIPVIZA randomized controlled trial, with single-arm cross-over

Abstract: Background Visual information about subclinical atherosclerosis was provided to physicians and participants in the VIPVIZA trial, inclusion 2013 to 2016 in northern Sweden, aiming to improve adherence to cardiovascular disease (CVD) prevention guidelines. Pictorial risk information may be more actionable. Aim Investigate the effect of intervention with pictorial risk information on time to first dispensing of statins. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
0
4
0
1
Order By: Relevance
“…Attached to the patient-related information to the physicians, guidelines for preventive treatment of patients with silent arthrosclerosis were also included. We have previously shown a clear increased rate of prescriptions of statins after the VIPIVZA intervention [ 11 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Attached to the patient-related information to the physicians, guidelines for preventive treatment of patients with silent arthrosclerosis were also included. We have previously shown a clear increased rate of prescriptions of statins after the VIPIVZA intervention [ 11 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…How this was experienced by and affected the participants was previously described [ 12 , 15 , 16 ]. How the intervention affects physicians’ prescriptions of statins and facilitates patient interaction and shortens time to initiation of statins has earlier been described [ 9 , 11 ]. In recent studies, the difference between men and women regarding both the patients’ and physicians’ view of CVD risk was highlighted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a qualitative evaluation of physicians experiences from receiving the VIPVIZA ultrasound information it was shown that the consultation became more patient-centred (Bengtsson et al, 2021a). Further, in a recently published evaluation on the intervention effect on physicians time to initiation of statin showed that after 3 years the average intensity of statin therapy was tripled in the intervention group (Holmberg et al, 2022). Previous results from VIPIVZA has shown that the LDL-cholesterol levels was significantly decreased in the intervention group at 3-year follow-up emphasising that the reduced progression of cIMT could be an effect of intensified lipid lowering therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Tato hodnota je jistě dobrou motivací ke změně životního stylu pro asymptomatické pacienty s aterosklerózou. Přímá vizualizace plátu a jeho předvedení pacientovi během vyšetření pak značně zkrátí čas, nutný k diskuzi nad zahájením terapie, a výrazně zlepši adherenci k dietním i farmakologickým opatřením (21,22).…”
Section: Běžná Vyšetřeníunclassified